1991
DOI: 10.1007/bf00041289
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting morphogenesis from immature cotyledons of Phaseolus coccineus L.

Abstract: Direct somatic embryogenesis as well as somatic embryogenesis and organogenesis mediated by small glossy calluses were obtained from immature cotyledon explants of bean (P. coccineus) cv Streamline 770 on a modified half-st~rength MS medium (Murashige & Skoog 1962) containing various concentrations of (2-isopentenyl)adenine and 2-naphthoxyacetic acid. Substitution of sucrose with glucose gave, in the range of concentrations tested, the strongest enhancement of the morphogenic process. Further improvement regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Types of calli were observed different in different orientations of explants such as green, compact and non embryogenic from vertically placed explants and yellowish whitish, friable, glossy and embryogenic callus in horizontally placed explants. Similar reports are there in Phaseolus coccineus (Genga and Allavena 1991). In contrast to our result, somatic embryo formation was observed on green compact hard callus in Desmodium motorium (Devi and Narmathabai 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Types of calli were observed different in different orientations of explants such as green, compact and non embryogenic from vertically placed explants and yellowish whitish, friable, glossy and embryogenic callus in horizontally placed explants. Similar reports are there in Phaseolus coccineus (Genga and Allavena 1991). In contrast to our result, somatic embryo formation was observed on green compact hard callus in Desmodium motorium (Devi and Narmathabai 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Sucrose and auxin concentrations have been found to interact with each other [70], with the optimal concentration· of one being dependent on the concentration of the other. Glucose was reported to be superior to sucrose for the induction of somatic embryos of the scarlet runner bean [71]. Galactose and lactose were reported to be superior to sucrose for the induction of somatic embryos from nucellar callus of citrus, while sucrose was more effective than glucose or fructose [72].…”
Section: Miscellaneous Factors a Genotype And Explant Characteristicsmentioning
confidence: 98%
“…In contrast, the present results demonstrated that higher concentrations of cytokinins did not favor embryo induction, but resulted in more callusing. On the other hand, somatic embryogenesis was effective with glucose in Phaseolus coccineus (Genga and Allavena 1991); maltose in Alfalfa sp. (Strickland et al 1987;Denchev et al 1991) and Glycine max (Finer and McMullen 1991); and the culture maintenance in darkness for many crop species (Thorpe 1988).…”
Section: Somatic Embryogenesismentioning
confidence: 99%